1997
DOI: 10.1017/s0022112097005843
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear corrections to Darcy's law at low Reynolds numbers

Abstract: Under fairly general assumptions, this paper shows that for periodic porous media, whose period is of the same order as that of the inclusion, the nonlinear correction to Darcy's law is quadratic in terms of the Reynolds number, i.e. cubic with respect to the seepage velocity. This claim is substantiated by reinspection of well-known experimental results, a mathematical proof (restricted to periodic porous media), and numerical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
130
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 5 publications
18
130
1
2
Order By: Relevance
“…2) is obtained for flow experiments on sand and gravel for a wide range of Reynold numbers (e.g., Moutsopoulos et al 2009;Sedghi-Asl et al 2014). Similar conclusions can be obtained from numerical studies, such as Firdaouss et al (1997) and Fourar et al (2004), which consider the Forchheimer equation (Eq. 2) valid over a wide range of Reynolds numbers.…”
Section: Nonlinear Laminar Flow and Fully Turbulent Flow In Porous Mediasupporting
confidence: 78%
“…2) is obtained for flow experiments on sand and gravel for a wide range of Reynold numbers (e.g., Moutsopoulos et al 2009;Sedghi-Asl et al 2014). Similar conclusions can be obtained from numerical studies, such as Firdaouss et al (1997) and Fourar et al (2004), which consider the Forchheimer equation (Eq. 2) valid over a wide range of Reynolds numbers.…”
Section: Nonlinear Laminar Flow and Fully Turbulent Flow In Porous Mediasupporting
confidence: 78%
“…That means that the pressure drop is considered as the sum of two terms: viscous (u, Darcy law) and inertia (u 2 ) terms. Several authors have shown that the onset of the non-linear behavior (that is sometime called the weak inertia regime) may be described by a cubic law (Firdaous et al, 1997;Mei & Auriault, 1993;Wodie & Levy, 1991):…”
Section: Flow Lawmentioning
confidence: 99%
“…4, was demonstrated by Schneebeli (1955). The nonlinear seepage flow law will be parabolic at Re [ 13, with deviation from linearity (Barenblatt et al 1990;Couland et al 1986); also nonlinear corrections to Darcy's law at low Reynolds numbers for periodic porous media have been described (Firdaouss et al 1997). Values of Reynolds number between 5 and 13 were calculated with numerical experiments based on the Navier-Stokes equations (Couland et al 1986;Stark 1972).…”
Section: Darcy and Couette Equationmentioning
confidence: 99%